The Creative and Cultural Industries towards Sustainability and Recovery - Komorowski, Marlen; Lewis, Justin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
During the last several decades, the creative and cultural industries (CCIs) have increasingly been recognized for their role in local, regional, national and supranational economies; as drivers of economic growth, development and regeneration; and for their social and cultural impact on well-being, place-making, inclusion, sustainability, diversity and culture. On the other hand, the COVID-19 crisis has exposed the fragility and precarity of an industry dominated by micro-businesses and freelance and informal work practices, as well as having few tangible assets, calling into question the sustainability of economic models based on a high level of precarity in labor practices. This has led to some efforts (by governments and public bodies) to protect the industry from the pandemic's impact. At the same time, lockdowns have also highlighted the importance of creative activity in maintaining individual well-being and community resilience as well as the innovative potential of the industry.In this context, this Special Issue addresses the broader research field of CCIs and its various subsectors, from media, arts, design, and more, as well as its role in developing pathways towards sustainability, resilience and recovery. This Special issue presents original research and the latest advances in both theoretical and practical approaches.